Origins of genuine Ohmic van der Waals contact between indium and MoS2 - Bum-Kyu Kim (Nature Portfolio, 2021)
Abstract The achievement of ultraclean Ohmic van der Waals (vdW) contacts at metal/transition-metal dichalcogenide (TMDC) interfaces would represent a critical step for the development of high-performance electronic and optoelectronic devices based on two-dimensional (2D) semiconductors. Herein, we report the fabrication of ultraclean vdW contacts between indium (In) and molybdenum disulfide (MoS2) and the clarification of the atomistic origins of its Ohmic-like transport properties. Atomically clean In/MoS2 vdW contacts are achieved by evaporating In with a relatively low thermal energy and subsequently cooling the substrate holder down to ~100 K by liquid nitrogen. We reveal that the high-quality In/MoS2 vdW contacts are characterized by a small interfacial charge transfer and the Ohmic-like transport based on the field-emission mechanism over a wide temperature range from 2.4 to 300 K. Accordingly, the contact resistance reaches ~600 Ω μm and ~1000 Ω μm at cryogenic temperatures for the few-layer and monolayer MoS2 cases, respectively. Density functional calculations show that the formation of large in-gap states due to the hybridization between In and MoS2 conduction band edge states is the microscopic origins of the Ohmic charge injection. We suggest that seeking a mechanism to generate strong density of in-gap states while maintaining the pristine contact geometry with marginal interfacial charge transfer could be a general strategy to simultaneously avoid Fermi-level pinning and minimize contact resistance for 2D vdW materials.